A Randomized Clinical Trial of Saccharomyces Cerevisiae Versus Placebo in the Irritable Bowel Syndrome (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: abdominal pain; irritable bowel syndrome; probiotic saccharomyces cerevisiae; yeast